2021
DOI: 10.1097/spv.0000000000001057
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes in Urogynecology—Assessment of Perioperative and Postoperative Complications Relative to Preoperative Hemoglobin A1c—A Fellows Pelvic Research Network Study

Abstract: Objectives: Poor control of diabetes mellitus is a known predictor of perioperative and postoperative complications. No literature to date has established a hemoglobin A 1c (HbA 1c ) cutoff for risk stratification in the urogynecology population. We sought to identify an HbA 1c threshold predictive of increased risk for perioperative and postoperative complications after pelvic reconstructive surgery.Methods: This multicenter retrospective cohort study involving 10 geographically diverse U.S. female pelvic med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that elevated preoperative HbA 1c is associated with increased rates of complications after urogynecologic surgery, especially when the HbA 1c level is above 8%. 8 These included higher rates of wound separation, urinary tract infections, fever, reoperation, and readmission. Higher HbA 1c levels have also been associated with higher rates of complications for patients undergoing midurethral sling surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that elevated preoperative HbA 1c is associated with increased rates of complications after urogynecologic surgery, especially when the HbA 1c level is above 8%. 8 These included higher rates of wound separation, urinary tract infections, fever, reoperation, and readmission. Higher HbA 1c levels have also been associated with higher rates of complications for patients undergoing midurethral sling surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These increased rates of complications lead to increased utilization of health care resources and increase costs for the health care system 5–7 . Studies have reported higher rates of complications among patients with elevated hemoglobin A 1C (HbA 1c ) levels above 8% undergoing female pelvic reconstructive surgery 8,9 . Many urogynecologic surgical procedures are considered elective and can be delayed or avoided if necessary to optimize outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The original study entitled "Surgical outcomes in urogynecologyassessment of perioperative and postoperative complications relative to preoperative hemoglobin A 1C " (the SUGAR study) was conducted through the American Urogynecologic Society and Society of Gynecologic Surgeons Group of the Fellows Pelvic Research Network (FPRN) and collected data on perioperative and postoperative complications on patients who underwent PRS performed by an FPMRS specialist in the abovementioned period. 6 Patients included in the study were female, 18 years or older, had a diagnosis of DM (defined by either an ICD-9 or ICD-10 code indicating the diagnosis, a documented diagnosis in the patient's medical history, or an HbA 1C value ≥6.5%), underwent PRS by an FPMRS specialist within the data collection period, and had a documented HbA 1C within 6 months before their surgery. Patients were excluded if they had surgery that was unrelated to the index prolapse/incontinence surgery, if they had a hysterectomy for reasons other than prolapse and had no other prolapse or incontinence surgery, or if data were unavailable (operative reports, discharge summaries, and/or outpatient records).…”
Section: Methodsmentioning
confidence: 99%
“…Ten to 20% of patients with UI or pelvic organ prolapse (POP) undergo pelvic reconstructive surgery (PRS), and some outcomes of PRS among patients with diabetes have been explored 4,5 . In a large multicenter retrospective study that sought to assess the relationship between preoperative HbA 1C and the risk of perioperative and postoperative complications after PRS among patients with DM, the authors found a 2- to 3-fold increase in the odds of developing postoperative complications with an A 1C of 8 or greater 6 . However, postoperative UI outcomes were not reported.…”
mentioning
confidence: 99%